Process technology for silicon carbide devices - Zetterling, Carl-Mikael (London, United Kingdom Institution of Engineering and Technology, 2002)
This book on the process technology for silicon carbide devices is divided into seven chapters. The first chapter discusses the material properties of SiC, and specifically the advantages of SiC that started the interest in the first place. This chapter also includes some basic calculations on high-voltage blocking and on-resistance. Chapters 2-6 cover the basic process steps used in fabricating SiC devices. The chapters cover bulk and epitaxial growth of SiC, ion implantation and diffusion, wet and dry etching, thermally grown and deposited dielectrics and Schottky and ohmic contacts. The final chapter, Chapter 7, covers devices in SiC, divided into different categories high-voltage devices, high-frequency devices, high-temperature, optical and mechanical devices.
Electronic reproduction.
Keywords: Silicon carbide -- Electric properties; Electronic books